The Influence of Purchasing Power and Economic Value of Property on Housing Sales Strategy - Tina Muhardika Handayani (Outline Journal of Economic Studies, 2026)
The purpose of this study was to analyze how purchasing power and the economic value of property influenced housing sales strategy within a dynamic real estate market. The research method employed a quantitative approach using primary data collected from 150 respondents and secondary data from industry and economic sources, which were then processed using multiple linear regression to examine both partial and simultaneous effects of the variables. The results indicated that purchasing power served as the most dominant factor shaping sales strategies, as consumers’ financial readiness strongly affected pricing policies, payment flexibility, and promotional approaches used by developers. The economic value of property also played a significant role, particularly in determining product positioning, perceived attractiveness, and the strategic emphasis placed on location, facilities, and investment potential. The conclusions drawn from this study emphasized that developers needed to integrate both consumer financial conditions and property value characteristics in order to formulate adaptive, targeted, and sustainable marketing strategies. The originality/value of this research lay in its combined assessment of purchasing power and economic property value within a single analytical model, offering a more comprehensive understanding of the determinants of housing sales strategies in contemporary property markets.